CIN85 Interacting Proteins in B Cells-Specific Role for SHIP-1 - Büchse, Tom (The American Society for Biochemistry and Molecular Biology, 2011)
The Cbl-interacting 85-kDa protein (CIN85) plays an important role as a negative regulator of signaling pathways induced by receptor tyrosine kinases. By assembling multiprotein complexes this versatile adaptor enhances receptor tyrosine kinase-activated clathrin-mediated endocytosis and reduces phosphatidylinositol-3-kinase-induced phosphatidylinositol-3,4,5-trisphosphate production. Here we report the expression of CIN85 in primary splenic B lymphocytes and the B-lymphoma cell lines WEHI 231 and Ba/F3. Cross-linking of the B cell antigen receptor resulted in an increased association of CIN85 with the ubiquitin ligase Cbl. Through a systematic pull-down proteomics approach we identified 51 proteins that interact with CIN85 in B cells, including proteins not shown previously to be CIN85-associated. Among these proteins, the SH2-containing inositol phosphatase 1 (SHIP-1) co-precipitated with both the full-length CIN85 and each of its three SH3 domains. We also showed that this association is constitutive and depends on a region of 79 amino acids near the carboxyl terminus of SHIP-1, a region rich in potential SH3 domain binding sites. Because SHIP-1 is a major negative regulator of the phosphatidylinositol-3-kinase pathway in lymphocytes, we hypothesize that the interaction between SHIP-1 and CIN85 might synergistically facilitate the down-regulation of phosphatidylinositol-3,4,5-trisphosphate levels.